Keanekaragaman dan Kunci Identifikasi Lalat Buah Berdasarkan Inang Tanaman Buah di Kabupaten Bangka, Bangka Belitung : Keanekaragaman dan Kunci Identifikasi Lalat Buah Berdasarkan Inang Tanaman Buah di Kabupaten Bangka, Bangka Belitung - Saputra, Herry Marta; Rahmawati, Venny; Apriyadi, Rion; Henri, Henri; Setiawan, Fahri (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Fruit flies are common pests of edible and commercial fruit crops. The presence of fruit flies can be detected using male attractant, but the species obtained mostly unknown on the host plant. The host rearing method for fruit infested with fruit flies can be use to see the distribution of host plant species and families. This research aims to determine the diversity of fruit flies pest species and the distribution of their host plants on horticultural fruit cultivated in Bangka Regency, Bangka Belitung Islands Province. A total of eight sub-districts in Bangka Regency surveyed using purposive sampling. The results showed that nine species of fruit plants were infested by six species of fruit flies. Five species of fruit flies have pest status, namely Bactrocera albistrigata, Bactrocera carambolae, Bactrocera dorsalis, Bactrocera sp1, and Zeugodacus cucurbitae and one species has non-pest status, namely Bactrocera mcgregori. Bactrocera dorsalis infested eight of the nine host plants. Bactrocera dorsalis, Bactrocera carambolae, and Bactrocera albistrigata were found in eight sub-districts. The fruit flies Bactrocera dorsalis and Bactrocera carambolae are the dominant species in Bangka Regency, Bangka Belitung.